PoSHAN Community Studies: Finding Pathways to Accelerate Nutritional Impacts. - Klemm, Rolf. (Tufts University. Tisch Library., 2016)
In this presentation Dr. Klemm reviews the data from the first PoSHAN community panel and points out changes that need to be made in the future panels. Keywords: Scientific Symposium, John Hopkins University.; Nutrition School: NIL Symposium Presentations, 2013.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy